Evaluation of hyaluronic matrix efficacy in sinus augmentation: a randomized-controlled histomorphometric and micro–computed tomography analysis. Issue 7 (July 2017) - Dogan, E.; Dursun, E.; Tosun, E.; Bilgic, E.; Akman, A.C.; Orhan, K.; Celik, H.H.; Korkusuz, P.; Caglayan, F.
Abstract: The objective of the present study was to test the hypothesis that the addition of hyaluronic acid–based matrix to collagenated heterologous bone graft for sinus augmentation would enhance bone formation compared to collagenated heterologous bone graft alone in the early healing period, by micro−computed tomography and histomorphometry. Thirteen systemically healthy patients requiring bilateral two-stage maxillary sinus augmentation (residual crest height ≤ 4 mm) were enrolled in this split-mouth prospective randomized controlled study. One sinus side as a control group was grafted with only collagenated heterologous bone graft; the other region as a test group was grafted with hyaluronic matrix and collagenated heterologous bone graft. Bone biopsy samples were taken after 4 months during the dental implant surgery and analyzed using micro−computed tomography and histomorphometric parameters. According to the micro−computed tomography and histomorphometric results, a significantly higher percentage of new bone was observed in the test group when compared to the control group after 4 months of healing. This study confirmed the hypothesis that the addition of hyaluronic matrix to collagenated heterologous bone graft for sinus augmentation enhances bone formation compared to collagenated heterologous bone graft alone in the early healing period.